EXPERIMENTAL STUDY OF THE EFFECTIVENESS OF TREATMENT OF WOOD DUST TO DUST COLLECTOR ENTERPRISES BUILDING INDUSTRY FOR COUNTER CORKSCREW FLOW - Sergei Igorevych Ekba; Pavel Alekseevich Sidyakin; Dmitri Pavlovich Borovkov; Denis Valerievich Azarov (Современная наука и инновации)
The reasons of ineffective operation of the dust removal equipment of the woodworking enterprises are analyzed. For cleaning of dust bursts of a woodworking use of dust collectors by the counter twirled flows with the conical separation camera is offered. Data of the pilot studies on optimization of characteristics of dust collectors by passers twirled to flows with the conical separation camera are provided, when trapping a wood dust.